Ability Leadership in Islamic Educational Institutions - Suriyadi Suriyadi; Nurapni Lelawati Siregar; Muhammad Rifai Harahap; Mesiono Mesiono (STAI Hubbulwathan Duri, 2022)
The attitude of leadership is an absolute thing inherent in a leader in an educational institution. This is because leaders are responsible for facilitating the development of human resources (HR) towards superior and complete people in the future. This study aims to analyze ability leadership in Islamic educational institutions. The background of this research is focused on 3 (three) units of Islamic educational institutions, namely MIN 1 Sahadabuan, MTsN 1 Padangsidimpuan Model, and MAN 2 Padangsidimpuan Model. This study uses a qualitative approach with descriptive analytical study method. Where the researcher seeks to reveal the facts in the phenomenon of the leadership of the 3 (three) institutions. The results of this study indicate that the Head of Madrasah has the same goal as the institution he leads, namely improving the quality of service and the quality of madrasas. The forms of ability leadership shown by the madrasa principal are (1) managerial skills including; implementing madrasa work programs, improving the quality and performance of teachers by involving teachers in education and training (training) and workshops, managing the rooms and offices of the teacher council; (2) Academic skills, including: providing opportunities for teachers to continue their studies (master and doctoral), providing general guidelines and services for teacher needs (administrative and academic), and carrying out academic supervision, and (3) communication skills, including: involving: teachers in decision-making efforts, appreciating teacher performance, providing motivation and advice to teachers collectively every month, forming a sense of kinship in madrasas. In addition, the madrasa head also seeks to function the madrasa environment as a Joint Learning Resource Center (PSBB).